Conducting Diagnoses of M&E Systems and Capacities - Shepherd, Geoffrey (World Bank, Washington, DC, 2012)
A diagnosis of a country's monitoring and evaluation (M&E) activities is indispensable if that country is to develop projects or policy proposals to improve the impact of M&E. This note provides a guide to some of the topics that need to be considered when undertaking such a diagnosis. These topics emphasize both the institutional analysis of factors that drive demand for M&E and the technical factors that drive supply. For each of the nine topics identified, this note discusses some of the major issues analysts would need to consider. This discussion principally centers on reviewing how these issues were covered in recent M&E studies for a number of developed and developing countries.